Molecular docking, synthesis and in vitro antimalarial evaluation of certain novel curcumin analogues - Chandrajit Dohutia; Dipak Chetia; Kabita Gogoi; Dibya Ranjan Bhattacharyya; Kishore Sarma (Universidade de São Paulo, 2018)
ABSTRACT The receptor protein PfATP6 has been identified as the common target of artemisinin and curcumin. The work was initiated to assess the antimalarial activity of six curcumin derivatives based on their binding affinities and correlating the in silico docking outcome with in vitro antimalarial screening results. A ligand library of thirty two Knoevenagel condensates of curcumin were designed and docked against PfATP6 protein and six compounds with the best binding scores were synthesized and screened for their antimalarial activity against the sensitive 3D7 strain of Plasmodium falciparum. ADME/Tox, pharmacokinetic and pharmacodynamic profiles of the designed compounds were analyzed and reported. 4-FB was found to have similar binding energy to the standard artemisinin (-6.75 and -6.73 respectively) while 4-MB, 3-HB, 2-HB, B, 4-NB displayed better binding energy than curcumin (-5.95, -5.89, -5.68, -5.35, -5.29 and -5.25 respectively). At a dose of 50 µg/mL all the six compounds showed 100% schizont inhibition while at 5µg/ml, five showed more than 75% inhibition and better results than curcumin. 4-FB showed the best activity with 97.8% schizonticidal activity. The in vitro results superimpose the results obtained from the in silico study thereby encouraging development of promising curcumin leads in the battle against malaria.